Revisiting Criminal Justice: From Retribution to Restoration in a Technological Era - Hermansyah (Indonesian Scientific Publication, 2025)
This narrative review explores contemporary challenges and reform trends in comparative criminal justice systems, emphasizing the interaction between retributive and restorative approaches and the integration of digital technologies such as artificial intelligence (AI). The study aimed to identify effective reform strategies and the systemic factors influencing their success. A comprehensive literature search was conducted across Scopus, Google Scholar, and other academic databases using Boolean operators to locate studies published in the last ten years, with inclusion criteria focusing on relevance, methodology, and language. Selected studies included qualitative, quantitative, and mixed-method research examining judicial systems in civil and common law countries. Results reveal that reform efforts are significantly shaped by institutional transparency, civic engagement, and corruption control. Countries like Rwanda and Germany demonstrated progress through inclusive reforms, whereas developing nations such as Indonesia face obstacles due to institutional limitations. Retributive models, particularly in the United States, contribute to high recidivism and neglect victims' needs. In contrast, restorative practices in Canada and New Zealand show enhanced outcomes in offender rehabilitation and victim satisfaction. Moreover, the use of AI in judicial systems, while improving efficiency, raises ethical concerns regarding algorithmic fairness and data governance. The findings highlight the urgent need for balanced policy frameworks that promote restorative justice, community engagement, and ethical integration of technology. Future research should examine adaptive models of justice reform suited to varying socio-political environments to enhance justice delivery globally.